Impact of myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) on the quality of life of people with ME/CFS and their partners and family members: an online cross-sectional survey - Vyas, Jui; Muirhead, Nina; Singh, Ravinder; Ephgrave, Rachel; Finlay, Andrew Y (BMJ open, 2022)
ObjectivesThe aim of this study was to assess the impact of myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) on the quality of life (QoL) of people with ME/CFS and their relative or partner (family member).DesignA patient-partner, multinational, subject-initiated, cross-sectional online survey.SettingInternational survey using ME/CFS charities, support groups and social media.ParticipantsParticipants were self-selected with recruitment via social media. Inclusion criteria were aged 18 years or over and reported diagnosis of ME/CFS by health professional. 1418 people with ME/CFS and their 1418 family members from 30 countries participated in the survey. Participants with ME/CFS had a mean age of 45.8 years (range 18–81) and were predominantly women (1214 (85.6%) of 1418). Family members had a mean age of 51.9 years (range 18–87) and were predominantly men (women: 504 (35.5%) of 1418). 991 (70%) family members were partners of the people with ME/CFS.InterventionsEuroQoL-5 Dimension (EQ-5D-3L), completed by people with ME/CFS, and Family Reported Outcome Measure (FROM-16) questionnaire, completed by family members.ResultsThe mean overall health status on a Visual Analogue Scale for people with ME/CFS was 33.8 (0=worst, 100=best). People with ME/CFS were most affected by ability to perform usual activities, pain, mobility, self-care and least impacted by anxiety. For family members, the overall mean FROM-16 score was 17.9 (0=no impact, 32=worst impact), demonstrating a major impact on QoL. Impact on QoL was significantly correlated between the person with ME/CFS and their family member (p<0.0001). Family members were most impacted emotionally by worry, frustration and sadness and personally by family activities, holidays, sex life and finances.ConclusionsTo the best of our knowledge, this is the largest study on the impact of the QoL of persons with ME/CFS and their family members. While open participation surveys are limited by selection bias, this research has revealed a significant worldwide burden of ME/CFS on the QoL of people with ME/CFS and their family members.